A proposal of risk indicators for pathological development from hemodynamic simulation: application to aortic dissection - Pan, Wenyang; Kulisa, Pascale; Bou-Saïd, Benyebka; El Hajem, Mahmoud; Simoëns, Serge; Sigovan, Monica (Journal of Cardiology and Cardiovascular Medicine, 2023)
Cardiovascular diseases are the leading cause of mortality in the industrialized world. Among these diseases, aortic dissection affects the aorta wall and is a surgical emergency with a low survival rate. This pathology occurs when an injury leads to a localized tear of the innermost layer of the aorta. It allows blood to flow between the layers of the aortic wall, forcing the layers apart and creating a false lumen. Endovascular treatment seeks to obliterate the entrances to the false lumen with a covered stent. There are very few studies on the postoperative demonstration of blood flow phenomena in the aortic dissection endovascular treatment. It is crucial to study the hemodynamics of blood in the aorta after an intervention because the new geometrical configuration of the aorta with a stent leads to modifications in blood flow. For the surgeons, the procedure can only be performed empirically, using MRI-4D images to view the postoperative flow of the patient’s blood in the aorta with the stent. This paper aims to present a numerical tool developed from the open-source software FOAM- Extend®, allowing for multiphysics numerical simulations. Using MRI data, a bio-faithful model of the patient-specific case was built. Numerical simulations were performed to predict preoperative and postoperative (endovascular treatment) hemodynamics. The modifications of the flow in the aorta were analyzed focusing on the postoperative perfusions. The results were compared with the corresponding MRI data and have a good qualitative agreement. Biomarkers are calculated to localize possible zones of post-operative pathological developments and recommendations may be suggested to the surgeons.